ANALISIS PENGARUH STRES KERJA DAN MOTIV ASI INTRINSIK TERHADAP KINERJA KARY A W AN DENGAN PENGALAMAN KERJA SEBAGAI VARIABEL PEMODERASI - Ni Putu Premierita Haryanti; I Komang Ardana (Faculty of Economics and Business Udayana University, 2014)
Thi s study aims to analyze the moderating role of work experience on the effect of work stress. The study wasconducted at the Bali Dynasty Resort Kuta with a sample of 84 people, selected by proportioned stratifiedrandom sampl ing method. Data were analyzed using Moderated Regression Analysis (MRA). It found thatwork experience was able to moderate stress whi le working on the performance of work experience was notable to moderate the influence of intrinsic motivation on performance. Head of the company should improveemployee performance through opt imal recruitment not ice and pay at tention to the work experience of theapplicants as well as providing information on employment status and length of employment to the peoplewho elected as an employee